Cardioprotective and hypotensive mechanistic insights of hydroethanolic extract of Cucumis melo L. kernels in isoprenaline-induced cardiotoxicity based on metabolomics and in silico electrophysiological models - Wahid, Muqeet; Saqib, Fatima; Abbas, Ghulam; Shah, Shahid; Alshammari, Abdulrahman; Albekairi, Thamer H.; Ali, Anam; Khurm, Muhammad; Mubarak, Mohammad S. (Frontiers in Pharmacology, 2024)
Background: Cardiovascular diseases (CVD) continue to threaten health worldwide, and account for a significant portion of deaths and illnesses. In both developing and industrialized nations, they challenge their health systems. There are several traditional uses of Cucurbitaceae seeds in Pakistan, India, Iran, and China, including treating cardiovascular, neurological, and urogenital diseases.In the present work, integrated techniques of metabolomics profiling and computational cardiomyocyte stimulation were used to investigate possible mechanisms of C. melo in isoprenaline (ISO)-induced myocardial infarction. In vitro, vasoconstrictions, paired atria, and in vivo invasive blood pressure measurement models were performed to explore the mechanism of action of C. melo hydroethanolic seed extract (Cm-EtOH).Results: Results showed that Cm-EtOH demonstrates NO-based endothelium-derived relaxing factor (EDRF) vasorelaxant response, negative chronotropic and inotropic response in the atrium, and hypotensive effects in normotensive rats. Results also revealed that Cm-EtOH decreases cardiomyocyte hypertrophy and reverts the altered gene expressions, biochemical, and metabolites in ISO-induced myocardial infarction (MI) rats. The extract additionally reversed ISO-induced MI-induced oxidative stress, energy consumption, and amino acid metabolism. Moreover, C. melo seeds increased EDRF function, energy production, and antioxidant capacity to treat myocardial and vascular disorders. In computational cardiomyocyte simulation, gallic acid reduced action potential duration, upstroke velocity (dV/dtmax), and effective refractory period.This study highlights the therapeutic potential of C. melo seeds to treat cardiovascular diseases and provides mechanistic insight into its antihypertensive and cardioprotective activities.